Assessment Accommodations for English Language Learners using the Student Language Assessment Plan - Sherri G. Brantley (The Advocate, 2015)
The purpose of this qualitative case study was to investigate the assessment accommodation process for English Language Learners (ELLs) on high-stakes testing (HST). It is understood the accommodation process is a challenge for school staff members that administer assessments to ELLs. This study addressed the problem of accountability and identification systems for ELLs by: (a) investigating the assessment accommodation process used by the study school; (b) understanding the perceptions of educators regarding the assessment accommodation process, and; (c) exploring the assessment accommodation tool used by educators to document appropriate accommodations for ELLs.